Experimental study of peptic ulcer. Heartburn against techniques gastrectomy - Baracco Gandolfo, Víctor (1956)
The experimental production of peptic ulcers similar to human is effected since the last century. To this end have been used a number of experiments that can be grouped considering "local factors" come into play (irritating the stomach, abdominal wall trauma, exposure to X-rays, infection, obstacles in the pyloric functions and duodenal and obstacles in the circulatory system), "systemic factors" that affect the stomach and duodenum (burns, cinchophen, immunization, nutrition disorders and endocrine disorders) and their experimental production "surgical procedures" (gastroenterostomy and diversion duodenal) secretions among those considered different factors, such as nutrition, acidity, mucosal susceptibility, mechanical factor, operative trauma, jejunal spasm and protective action of duodenal secretions.